Investigation into Critical Gut Microbes Influencing Intramuscular Fat Deposition in Min Pigs - Long Jin; Ke Li; Zhimin Li; Xuankai Huang; Li Wang; Xibiao Wang; Shengwei Di; Shiquan Cui; Yuan Xu (Animals)
To determine the pivotal microorganisms affecting intramuscular fat (IMF) accumulation in Min pigs and to discern the extent of the influence exerted by various intestinal segments on IMF-related traits, we sequenced 16S rRNA from the contents of six intestinal segments from a high IMF group (Group H) and a low IMF group (Group L) of Min pigs weighing 90 ± 1 kg. We then compared their diversity and disparities in bacterial genera. Group H exhibited considerably higher α diversity in the jejunum and colon than Group L (p < 0.05). When 95% confidence levels were considered, the main β diversity components for the ileum, caecum, and colon within Groups H and L exhibited absolute segregation. Accordingly, 31 differentially abundant genera across Group H were pinpointed via LEfSe and the Wilcoxon test (p < 0.05) and subsequently scrutinised based on their distribution and abundance across distinct intestinal segments and their correlation with IMF phenotypes. The abundances of Terrisporobacter, Acetitomaculum, Bacteroides, Fibrobacter, Treponema, Akkermansia, Blautia, Clostridium sensu stricto 1, Turicibacter, Subdoligranulum, the [Eubacterium] siraeum group, and dgA 11 gut groups were positively correlated with IMF content (p < 0.05), whereas those of Bacillus, the Lachnospiraceae NK4A136 group, Streptococcus, Roseburia, Solobacterium, Veillonella, Lactobacillus, the Rikenellaceae RC9 gut group, Anaerovibrio, and the Lachnospiraceae AC2044 group were negatively associated with IMF content (p < 0.05). Employing PICRUSt2 for predicting intergenic metabolic pathways that differ among intestinal microbial communities revealed that within the 95% confidence interval the colonic microbiome was enriched with the most metabolic pathways, including those related to lipid metabolism. The diversity results, bacterial genus distributions, and metabolic pathway disparities revealed the colonic segment as an influential region for IMF deposition.